Diagnostic Yield of Acid Fast Bacilli in Bronchoalveolar Lavage of Sputum-Negative Pulmonary Tuberculosis Patients - Janjua, Tehreem Zulfiqar; Musharaf, Saqib; Janjua, Arooba Zulfiqar; Chaudhery, Faisal Hassan Zahid; Bakhtawar, Farzeen; Ashraf, Anum (Biological and Clinical Sciences Research Journal, 2025)
Pulmonary tuberculosis (PTB) remains a significant public health concern, especially in high-burden countries like Pakistan. Diagnosis becomes particularly challenging in sputum-negative patients, leading to delayed treatment and increased transmission. Bronchoalveolar lavage (BAL) has emerged as a potential diagnostic tool in such cases. Objective: To determine the diagnostic yield of acid-fast bacilli (AFB) in bronchoalveolar lavage of sputum-negative pulmonary tuberculosis patients. Methods: This cross-sectional study was conducted in the Department of Pulmonology, Gulab Devi Hospital, Lahore, over six months from June to December 2024. One hundred fifty sputum-negative PTB patients undergoing BAL were enrolled through consecutive sampling. BAL samples were collected and sent to the pathology laboratory for AFB testing via Ziehl-Neelsen staining. The primary outcome was the proportion of positive AFB results among the study population. Data were analyzed using SPSS version 25. Chi-square test was applied to assess associations between diagnostic yield and demographic or clinical variables; a p-value < 0.05 was considered statistically significant. Results: Among 150 patients, 71.3% (n = 107) were male; the mean age was 42.81 ± 11.23 years. Most participants (72.0%) were aged ≤45 years. A majority (68.0%) resided in rural areas, and 62.7% belonged to a low socioeconomic status. Comorbidities included diabetes (32.7%), hypertension (40.7%), and obesity (9.3%). The mean disease duration was 2.36 ± 1.09 months, with 80.7% having symptoms for ≤3 Months. Family history of TB and smoking history were noted in 26.0% and 22.0%, respectively. Most patients were unskilled workers (47.3%) or housewives (24.0%). The diagnostic yield of BAL for AFB was 83.3% (n = 125). Diagnostic yield was significantly associated with gender (p < 0.05), residential status (p < 0.05), disease duration (p < 0.05), and occupation (p < 0.05). Conclusion: Bronchoalveolar lavage demonstrates a high diagnostic yield for AFB in sputum-negative PTB patients and should be incorporated as a standard diagnostic modality in suspected cases. Early and accurate diagnosis through BAL can facilitate timely management, reduce disease transmission, and improve patient outcomes, particularly in resource-limited settings.